Synthesis of Molybdenum Borides by the Impact of an A.C. Arc Discharge in Air; Journal of Engineering Physics and Thermophysics; Vol. 98, iss. 5 - Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Neklya Yu. A. Yuliya Aleksandrovna; Speransky M. Yu. Maksim Yurjevich; Pak A. Ya. Aleksandr Yakovlevich (2025, 2025)
The authors have pioneered in describing the method of obtaining molybdenum-boride crystalline phases through the impact of an a.c. arc discharge on the starting mixture that contains molybdenum and boron powders in an open air medium at atmospheric pressure. In the work, a study has been made of the dependences of the influence of the regime parameters of an original arc reactor, such as the current strength of a power supply and the duration of the arc discharge, on the phase composition of synthesis products. It has been established that during the treatment of the starting mixture which contains molybdenum and boron powders in the atomic ratio Mo/B = 1/15 by an atmospheric a.c. arc discharge for 50 s at a current strength of 300 A, a full processing of the starting components to form molybdenum boride is ensured. The formation of the following molybdenum-boride crystalline phases has been recorded: Mo2B, α-MoB, MoB2, and Mo2B5. The obtained results allow extending the field of application of a vacuum-free electric-arc method